On the electrophonic generation of audio frequency sound by meteors - Michael C. Kelley; Colin Price (Geophysical Research Letters)
Abstract Recorded for centuries, people can hear and see meteors nearly concurrently. Electromagnetic energy clearly propagates at the speed of light and converts to sound (called electrophonics) when coupled to metals. An explanation for the electromagnetic energy source is suggested. Coma ions around the meteor head can easily travel across magnetic field lines up to ~120 km. The electrons, however, are tied to magnetic field lines, since they must gyrate around the field above ~75 km. A large ambipolar electric field must be generated to conserve charge neutrality. This localized electric field maps to the E region then drives a large Hall current that launches the electromagnetic wave. Using antenna theory and following, a power flux of over 10−8 W/m2 at the ground is found. Electrophonic conversion to sound efficiency then needs to be only 0.1% to explain why humans can hear and see meteors nearly concurrently.